Trade union movement and labor market in the Côte d’Ivoire - Dago, Beugre Ange Emmanuel (International journal of economic perspectives, 2025)
This article aims to shed light on the existence of a relationship between trade union activities and overall unemployment (male and female unemployment) in the Côte d’Ivoire labor market. Using Denton’s method, we converted our annual data covering 2011-2021 into quarterly data. Furthermore, an ARDL model indicates that trade union action within companies is a growing source of overall unemployment in Côte d’Ivoire. In other words, this unionisation rate, which can be used to estimate employees’ bargaining power vis-à-vis employers, is hindering the decline in the overall unemployment rate (for both men and women) in the Côte d’Ivoire labor market. In fact, a 1% increase in union membership leads to a 2.58% increase in the overall unemployment rate (1.40% for male job seekers and 2.27% for female job seekers). Thus, in terms of economic policy implications, the introduction of a policy aimed at encouraging competition in product markets in order to eliminate the negative effects of trade unions will indeed be very beneficial for job seekers.